Under-Age and Forced Marriages: An Anathema of the Pakistani Society - Ahmad Nawaz (Journal of Public Policy Practitioners, 2022)
Child marriage as a social norm has been in practice in most societies around the world. Socio-political and scientific development in the last few decades popularized the harmful consequences of this practice on victims’ emotional and physical health, their educational attainment, impairment of their employment opportunities, and gender parity. The global conscience under United Nations (UN) acknowledged the right to enter into marriage with free and full consent as a basic human right, thus appreciating the ramification of this practice at individual level. Pakistan is signatory to various international treaties that aim to curb the practice of child marriage. Moreover, meeting the commitments under these instruments also introduced some reforms in the legal framework that deals with this practice. There are, however, issues of socio-cultural traditions along with religious beliefs and economic compulsions that contribute in the continuation of this practice in Pakistan. The current paper attempts to contribute in the appraisal of the existing legal framework on the subject, analyzes the determinants of this practice, and explores their causal relationship in the context of Pakistan’s socio-cultural norms. Data analysis from various reports of Pakistan Demographic and Health Survey shows that the economic determinants of poverty and education attainment predominantly influence the age at which girls are married. Afterwards, owing to their limited social exposure and level of education, the parents of poor and rural household are more likely to be influenced by orthodox socio-cultural traditions and religious dogmas. Relying on an evidencebased analysis, the current study derives that any meaningful policy initiative to curb this practice must primarily focus on educational attainment and poverty alleviation of vulnerable population. Besides, a well-knit awareness campaign needs to be carried out in order to clarify the misinterpretation of Islamic teachings related to girl’s maturity and the preferred age for marriage along with highlighting the harmful consequences of child marriage.